Enhancing Digital Literacy Skills for Students and Teachers - Mustika, Maya; Fadillah, Hanifah Tri Nur; Gymnastia, Hanifa Najla; Ghessiani, Luthfiannisa; Amaliyah, Siska; Al Fasihah, Tamamatunnisa (Santoso Academy Network, 2025)
Basic computer skills and the ability to utilize technology-based learning media are essential competencies in the digital era. This program was designed to strengthen community benefits by introducing fifth-grade students to the use of personal computers as a foundation for digital literacy, while simultaneously improving teachers’ competence in applying digital learning media at SDN Sukamulya 01. The activities, carried out from April to June 2024 for students and in May 2024 for teachers, included training sessions, hands-on practice, and mentoring. The program demonstrated tangible impacts: 75% of students were able to operate PCs independently, indicating a significant increase in digital literacy skills. In addition, all participating teachers (100%) successfully produced simple digital learning media using available applications, reflecting enhanced teaching competence and the program’s overall contribution to community capacity building.